Effect of Climate Change on Small Scale Agricultural Production and Food Security in Kitui District, Kenya - Khisa, Gladys V.; Oteng’i, S. B.; Mikalitsa, S. M. (World Science and Research Publishing, 2014)
Most of the world’s arid and semi-arid lands (ASALs) are found in the developing countries. These ASALs face many challenges some of which are as a result of the declining availability of water resources and increasing threats from climate change. Climate change is expected to affect the availability of freshwater worldwide, the productivity and fertility of soils, and amount of food produced by farmers in the tropical countries majority of which are developing countries. While contributing the least to global warming, it is the developing countries that will suffer the most from it, having the least capacity to adapt. Kitui District is one of the semi-arid districts in Kenya where the impact of climate change has been seriously felt. This paper examines the effect of climate change on food production and security among small scale farmers in the semi-arid region of Kitui District. Various methods were employed in data collection among them structured questionnaires, oral interviews with key informants, focus group discussion and direct observation. The collected data was analyzed using both descriptive and inferential statistics. The results show that most farmers (87.5% n=350) had less than five acres of land which was not enough to grow adequate food for the household, did not have an alternative source of income (78.5%, n =314) and experienced reduced agricultural production due to reduced rainfall (97%, n =388). There was a significant difference between the size of the farm and land use (χ2=143.492, df=1, P=0.000). The results indicate climate change has had a negative effect on food production; the temperatures are increasing, extreme climatic conditions have become more frequent while the amount and frequency of rainfall have reduced considerably. This has led to a reduction in agricultural production in the district which has consequently resulted in food shortages in the household. The results also show that very few of the farmers have adopted coping strategies against the effects of the changing climate. It recommends that small scale farmers need to be assisted financially and technically to enable them employ coping strategies that would cushion their agricultural activities against the harmful effects of climate change.
Keywords: Climate change; Agricultural production; Food security